Preservação ambiental e qualidade de vida em comunidades quilombolas - Nishijima, Toshio; Martins, Luciana Aparecida Ramos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
This study aimed to understand the reality of the “quilombola” community, evaluatingtheir successes and their needs, looking for community awareness regarding the importance ofenvironmental preservation, as well as its correlation with the health and quality of life forresidents of the Passo do Maia, located in Formigueiro city, in the central region of Rio Grande doSul state, Brazil. The first step came from analysis and interpretation of different approaches tothe topic found in references, both in relation to the historical formation of “quilombola”communities, and in specific works on the environment, environmental preservation and properdisposal of household waste. The second stage was based on information gathered frominterviews and questionnaires administered to community residents. Among the main problems ofenvironmental degradation in the community, there is the pollution of waters and soils due to the improper disposal of domestic waste, which are often deposited in the environment. You canimprove the surroundings, based on appropriate practices in relation to household wasteproduced in the community, such as separating waste, and organics can or should be buried inorder to be used as organic fertilizer in their gardens in the existing location. Awareness amongcommunity residents on the issue of environmental preservation is possible, as demonstratedwillingness to adopt new habits more environmentally healthy, with the use of pedagogicalpractices of environmental education.